Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Media PheT Terhadap Kemampuan Pemecahan Masalah dan Berpikir Kritis Fisika Peserta Didik SMA - Kurnia Agustina; Hairunnisyah Sahidu; I Wayan Gunada (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aimed to determine the effect of PhET media guided inquiry learning model toward the problem solving and critical thinking skills of high school students. This type of research was quasi-experimental research design with pretest-posttest control group design. The population was all students of class X IPA of SMAN 1 Jereweh in the 2018/2019 academic year. The samples were taken using purposive sampling technique and obtained class X IPA 1 as an experimental class and class X IPA 2 as a control class. The independent variable of guided inquiry learning model assisted by PhET media that was ÃÂ imposed on the experimental class, while the ability to solve problems and critical thinkingÃÂ  as the dependent variable. The data were taken using essay tests to measure students' problem solving and critical thinking skills. The research hypothesis was tested using the Manova test with a significant level of 5% aided by IBM SPSS 23 and the results of the hypothesis test showed a significant 0.028 so Ha was accepted because sig. <0.05.Based on these results it can be concluded that there wasÃÂ  an effect of the treatment of guided inquiry model assisted by PhET media on the students'physicsproblem solvingÃÂ  and critical thinking skills at senior high school.